The psychology of gender - Wood, Gary (Psychologist) (Abingdon, Oxon ; New York, NY : Routledge, an imprint of the Taylor & Francis Group, 2018)
What is the difference between sex and gender? What is the impact of gender-role stereotypes on our lives, our relationships and the world? What does gender mean to you? The Psychology of Gender looks at our biology, history and culture to consider the impact of gender roles and stereotypes, and addresses the 'dilemmas' we have regarding gender in a post-modern world. It offers a unique perspective on gender through storytelling and explores ideas around transgender and cisgender identities and androgyny, tackling hidden assumptions and helping us make sense of the world of gender. By examining the future of gender, The Psychology of Gender offers a platform for further exploration, and arrives at a new psychology of gender that emphasises relationships and helps us to understand our own gender identity and that of those around us
Includes bibliographical references (pages [95]-109)
Keywords: Sex differences (Psychology); Sex role -- Psychological aspects; Print books